2021
DOI: 10.3390/su13020780
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Relational Capital in Anti-Crisis Measures Undertaken by Companies—Conclusions from a Case Study

Abstract: The aim of this article was to present the results of empirical research conducted in enterprises of all sizes operating in Poland and Central Europe. The study focused on the impact of relational capital on the prevention of and intervention in the event of a crisis in a company. The author assumes that there is a link between a company’s relational capital and its susceptibility to crisis phenomena. The research carried out allowed different conclusions to be drawn. It turns out that the studied companies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…Later, Morgan (1996) undertook more thorough investigations of relational capital, highlighting the fact that it is a non-market resource that resides outside the organization and has the potential to provide value to it. Relational capital is defined as the sum of relationships among a firm and its key business parties and is operationally defined via factors such as image, customer satisfaction and loyalty, connections with suppliers, environmental activities, commercial power, negotiation skills with financial enterprises, and so forth (Walecka, 2021). RC is described as the relationship a firm develops with its internal and external stakeholders, including its clients, suppliers, staff, and partners in strategic alliances (Ordonez de Pablos, 2003).…”
Section: Relational Capitalmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Morgan (1996) undertook more thorough investigations of relational capital, highlighting the fact that it is a non-market resource that resides outside the organization and has the potential to provide value to it. Relational capital is defined as the sum of relationships among a firm and its key business parties and is operationally defined via factors such as image, customer satisfaction and loyalty, connections with suppliers, environmental activities, commercial power, negotiation skills with financial enterprises, and so forth (Walecka, 2021). RC is described as the relationship a firm develops with its internal and external stakeholders, including its clients, suppliers, staff, and partners in strategic alliances (Ordonez de Pablos, 2003).…”
Section: Relational Capitalmentioning
confidence: 99%
“…The review of the literature conducted by Walecka (2021) on relational capital and crises in enterprises revealed that both of these topics have not been sufficiently investigated. It is important to emphasize that although there is a wealth of research in the field of crisis management regarding determinants of enterprises’ resilience to crises; it rarely emphasizes the significance of RC as a means in anti-crisis strategies ( Walecka, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For the purposes of the paper, it has been assumed that relational capital is understood to mean all relations of a company with its environment , especially with customers, competitors, suppliers and strategic allies, financial institutions, local government, labour market institutions, and other stakeholders (Walecka and Zelek, 2017). It is the entirety of relations and ties between a company and its stakeholders (Walecka, 2020;2021).…”
Section: Customer Relations As An Element Of a Company's Relational Capitalmentioning
confidence: 99%
“…Several studies have documented the different approaches to the concept of "crisis management" within different sectors of the economy or particular business entities. In particular, evidence suggests that there is a link between the relational capital of the business entity and its susceptibility to crisis phenomena (Walecka 2021;Macerinskiene and Survilaite 2019). Some existing research recognizes the critical role played by crisis management within the different stages of company development, with consideration to a wide range of crisis-prevention methods and instruments (Meiste and Jakstiene 2015).…”
Section: Introduction and Review Of Literaturementioning
confidence: 99%